Discovery Learning Model Optimizing Digital Thematic Multilingual Dictionary to Improve Literacy Skills - Ni Made Ratminingsih; I Gede Budasi; Made Hery Santosa; Ni Nyoman Padmadewi; Luh Putu Artini; I Putu Yoga Purandina (Universitas Pendidikan Ganesha, 2023)
A preliminary study found that the students faced literacy skill problems. The results of pre-tests proved that the mean score achieved by grade 4 was 42.49 (very low), grade 5 was 63.06 (low), and grade 6 was 49.58 (very low). Regarding these findings, this study further aimed to analyze whether implementing a discovery learning model that optimized a digital thematic multilingual dictionary could improve the elementary students’ literacy skills. This study involved four main steps, plan, act, observe, and reflect. The samples were 84 students determined purposively for deciding three classes among those nine classes representing 4th, 5th, and 6th grades. There were two kinds of tests, pre-test and post-test. The pre-tests were used to measure the literacy level before treatments, while the post-tests were employed to count for the literacy level after treatment. After four sessions of treatments and two post-tests, it was discovered that students' literacy skills could have been notably improved. The mean scores obtained on the second cycle, respectively, were 86.77 (high), 93.66 (very high), and 95.55 (very high). These results imply that the discovery learning model utilizing a digital thematic multilingual dictionary can enhance elementary school students’ literacy skills. Thus, it is strongly recommended that students regularly use dictionaries for their self-directed learning.